COMPARATIVE HYPOGLYCEMIC ACTIVITY OF GLYCYRRHIZIC ACID AND GYMNEMIC ACID ON NON-INSULIN DEPENDENT RODENT DIABETIC MODEL - S. SINGH,; P. BIGONIYA,; B. SHRIVASTAVA, (International Journal of Pharma and Bio Sciences, 2015)
This study investigates the comparative anti-diabetic activity of glycyrrhizic acid and gymnemic acid on non-insulin dependent diabetic models i.e. oral glucose tolerance (OGTT), adrenalin and dexamethasone induced diabetes. Glycyrrhizic acid and gymnemic acid were isolated from crude extract of Glycyrrhiza glabra and Gymnema sylvestre and authenticated by co -TLC with standard. Invivo antidiabetic profile was assessed at 50 and 100 mg/kg for glycyrrhizic acid, and 30 and 60 mg/kg for gymnemic acid dose along with a combination of higher doses on OGTT, adrenalin and dexamethasone induced diabetes on rats. Glycyrrhizic acid at both the doses significantly (P<0.05-0.001) reduced blood glucose peak in OGTT whereas gymnemic acid lowers the glucose peak only at high dose (p<0.01). Glycyrrhizic acid and gymnemic acid, both caused highly significant (P<0.001) reduction of the hypoglycemic response induced by adrenaline and dexamethasone. Combination very efficiently reduced the adrenalin and dexamethasone-induced hyperglycemia and showed additive action on OGTT. Glycyrrhizic acid has efficient oral glucose tolerance and reversal action on adrenalin induced hyperglycemia due to improved peripheral glucose uptake and utilization. Gymnemic acid has moderately increased glucose tolerance and decreased adrenalin induced hyperglycemia by slowing the intestinal absorption and increasing insulin secretion. Combination of glycyrrhizic acid and gymnemic acid exerts better anti-hyperglycemic action against both adrenalin and dexamethasone signifying their ability to rectify metabolic non-insulin dependent adrenocortical system related hyperglycemia probably by enhancing glucose sensitized insulin release. The study outcome signifies promising role glycyrrhizic acid and gymnemic acid in the management of non-insulin dependent diabetes.